The Top Ten Websites in Critical Care Medicine Education Today. (January 2019) - Wolbrink, Traci A.; Rubin, Lucy; Burns, Jeffrey P.; Markovitz, Barry
Introduction: The number of websites for the critical care provider is rapidly growing, including websites that are part of the Free Open Access Med(ical ed)ucation (FOAM) movement. With this rapidly expanding number of websites, critical appraisal is needed to identify quality websites. The last major review of critical care websites was published in 2011, and thus a new review of the websites relevant to the critical care clinician is necessary. Methods: A new assessment tool for evaluating critical care medicine education websites, the Critical Care Medical Education Website Quality Evaluation Tool (CCMEWQET), was modified from existing tools. A PubMed and Startpage search from 2007 to 2017 was conducted to identify websites relevant to critical care medicine education. These websites were scored based on the CCMEWQET. Results: Ninety-seven websites relevant for critical care medicine education were identified and scored, and the top ten websites were described in detail. Common types of resources available on these websites included blog posts, podcasts, videos, online journal clubs, and interactive components such as quizzes. Almost one quarter of websites (n = 22) classified themselves as FOAM websites. The top ten websites most often included an editorial process, high-quality and appropriately attributed graphics and multimedia, scored much higher for comprehensiveness and ease of access, and included opportunities for interactive learning. Conclusion: Many excellent online resources for critical care medicine education currently exist, and the number is likely to continue to increase. Opportunities for improvement in many websites include more active engagement of learners, upgrading navigation abilities, incorporating an editorial process, and providing appropriate attribution for graphics and media.